The Old Testament and Christian Spirituality : Theoretical and Practical Essays from a South African Perspective - Lombaard, Christo (Society of Biblical Literature, 2012)
After a three-page introduction, Lombaard, professor of Christian spirituality in the College of Human Sciences at the University of South Africa, presents essays on the following topics: the OT in Christian spirituality–perspectives on the undervaluation of the OT in Christian spirituality; four South African proposals for a central theme to "scriptural spirituality"; four recent books on spirituality and the Psalms–some contextualizing, analytical, and evaluative remarks; genealogies and spirituality in Gen 4:17-22, 25-26 and 5:1-32; What is biblical spirituality?–perspectives from a minor genre of OT scholarship; between text and nature, God, and evolution–biblical reception and creationism, at the Creation Museum in cultural-anthropological perspective; and exegesis and spirituality. An electronic open access edition is available at http://ivbs.sbl-site.org/home.aspx Abstract Number: NTA57-2013-1
paid
Keywords: Biblical Theology.